Allergen Immunotherapy–Induced Immunoglobulin G4 Reduces Basophil Activation in House Dust Mite–Allergic Asthma Patients - Feng, Mulin; Zeng, Xiaohui; Su, Qiujuan; Shi, Xu; Xian, Mo; Qin, Rundong; Li, Jing (Frontiers in Cell and Developmental Biology, 2020)
Whether allergen immunotherapy (AIT) could reduce allergy effector cell activation is unclear. We aimed to evaluate the basophil response during Dermatophagoides pteronyssinus (Der p) subcutaneous immunotherapy (SCIT) and its relationship to allergen specific IgG4 (sIgG4) in allergic rhinitis and/or asthma patients. The study included a total of 55 subjects, of which 35 cases received Der p SCIT and 20 controls received regular medications. Symptom and medication scores (SMS), sIgG4 levels, specific IgE (sIgE) levels, allergen-induced basophil activation test (BAT) in whole blood, and BAT inhibition assays in serum were determined at weeks 0, 4, 12, 16, 52, and 104 of SCIT. We found that levels of Der p sIgG4 showed a significant increase after SCIT. Serum obtained from SCIT patients significantly inhibited basophil activation after 12 weeks of treatment. Removal of IgG4 antibodies at week 104 reduced the ability of serum to block basophil activation. Increase of Der p sIgG4 rather than reduce of Der p sIgE correlate with the reduction of basophil activation during SCIT. The sIgG4 antibodies might compete with sIgE binding to allergen to form IgE-allergen complex. In conclusion, SCIT reduced the sensitivity of allergen-triggered basophil activation in Der p allergic rhinitis and/or asthma patients through induction of sIgG4.